William Faulkner as an Experimental, modern novelist in as I lay Dying (1930) - Ibrahim, Juan Abdulla (International Journal of Psychosocial Rehabilitation, 2020)
Faulkner, the American modern novelist, experiments in his novel As I Lay Dying, by concentrating on the way the mind of the characters in the novel work. Through the way the character’s think and feel, they pass through sensitive stages of irritation and misery through a journey, when they take their mother, Addie Bundren’s coffin to Jefferson, where her family cemetery lies. This journey is a sign of the absence of spirituality in the modern world. It is about selfishness of the individuals. Each character responds differently to the death of their mother in the novel. Faulkner through the analysis of thoughts and feelings of these characters who were members of Bundren family concludes how the mind of human beings is complex and each mind responds differently. The concept of death in the text is viewed and analysed due to the modernist and existential approach. Faulkner introduces poverty as problematic and links its consequences to Addie’s considering death as an escape and relief from its problems and her monologues are indications of her femininity and her refusal of a silence in a patriarchal society. Faulkner’s message is that mother has an active role in the family, even after her death, her impact remains..